Migration behavior and dietary exposure risk assessment of pesticides residues in honeysuckle (Lonicera japonica Thunb.) based on modified QuEChERS method coupled with tandem mass spectrometry. (April 2023) - Li, Qianqian; Zhang, Jialin; Lin, Tao; Fan, Chunlin; Li, Yi; Zhang, Zijuan; Li, Jianxun
Graphical abstract: Highlights: Modified QuEChERS methods were established to determine 93 pesticides in honeysuckle. The migration behavior was explored for risk assessment evaluation. 86.02% of 93 honeysuckle samples were contaminated by at least one pesticide. Both the chronic and the acute exposure yielded no hazardous to adults and children. Abstract: The honeysuckle was widely appreciated as tea beverage owing to the biological activities and the unique aroma and flavor. It is in urgent requirement to explore the migration behavior and dietary exposure as the pesticide residues would bring about potential risks through honeysuckle intake. The optimized QuEChERS procedure coupled with the HPLC-MS/MS and GC-MS/MS methods were employed to determine 93 pesticide residues of seven classifications including carbamates, pyrethroid, triazoles, neonicotinoids, organophosphorus, organochlorine, and others for 93 honeysuckle samples from four primary production bases. As a result, 86.02% of the samples were contaminated by at least one pesticide. Unexpectedly, the banned pesticide of carbofuran was also identified. The migration behavior of metolcarb was the highest, whereas thiabendazole contributed less risk to the infusion with relative lower transfer rate. Both the chronic and acute exposure yielded low risk for human health with five high risk pesticides of dichlorvos, cyhalothrin, carbofuran, ethomyl, and pyridaben. Besides, this study provides foundation of dietary exposure risk assessment for honeysuckle and other likewise products.